Do mito da tecnologia ao paradigma tecnológico; a mediação tecnológica nas práticas didático-pedagógicas - Maria Rita Oliveira Neto Sales (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
The main objective of the text is to present a critical perspective on technology in education and teaching. Three hypotheses are discussed: educational technology revisited, the competence model and the myth of technology. The text also discusses the characteristics of the new technological paradigm and some aspects of The green book published by the brazilian Ministry of Science and Technology. In conclusion, the article points to some of the implications linked to a critical understanding and treatment of technology in teaching and educational practice.